Fetal MRI diagnosis of brainstem disconnection with novel inner ear anomalies. (5th July 2014) - Carr, John Robertson; Brandon, Jonathan; Ross, Benjamin; Bryant, Sean Olof
<x xml:space="preserve">Abstract</x> What is already known about this topic? Brainstem disconnection (BD) is a very rare, lethal, and poorly understood congenital anomaly diagnosed typically on neonatal MRI and never before diagnosed by fetal MRI. The etiology is unclear. What does this study add? This is the first prospective diagnosis of BD by fetal MRI, and our case has an additional novel inner ear anomaly further supporting a genetic etiology.